Continuing Education A Management Point of View - Williams, J. D. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
The needs for continuing engineering education to avoid technical obsolescence and the programs offered by one company to fill this need are discussed. Ten educational alternative programs of the Sandia Laboratories, Albuquerque (New Mexico) are described. (CP)
ERIC Note: Paper presented at the Annual Meeting of the American Society for Engineering Education (Colorado State University, Ft. Collins, Colorado, June 16-19, 1975).
Educational level discussed: Adult Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Education; Adult Education; Apprenticeships; Engineering Education; Independent Study; Industrial Education; Industry; Obsolescence; Program Descriptions; Science Education; Technical Education; Speeches/Meeting Papers